Increase in irrigated wheat yield in north-west Mexico from 1960 to 2019: Unravelling the negative relationship to minimum temperature - Fischer, Tonya; Honsdorf, Nora; Lilley, Julianne; Mondal, Suchismita; Ortíz Monasterio, Jose Iván; Verhulst, Nele (Elsevier, 2022)
Conservation agriculture (CA) systems represent a set of three soil management principles: minimarbance, permanent soil cover and crop rotations ‐ whereas the CA‐based systems in this study add the bed and furrow tillage techniques as integral elements of CA. Studies on the effects of long‐term CA‐based systems on soil health and crop productivity are rare globally, particularly in Ethiopia. This study aimed at investigating the long‐term (2005–2013) influence of CA‐based systems on soil health and crop productivity in northern Ethiopia. The treatments we used include two types of CA‐based systems (permanent raised bed PRB and contour furrowing CF) and conventional tillage (CT) arranged in a randomized complete block design. Soil samples were collected at 0–10 cm soil depth to assess soil health. Piecewise structural equation modeling (PSEM) was used to analyze linkages between management practices, soil health and crop productivity. Arbuscular mycorrhizal fungi spore abundance and root colonization was higher in PRB followed by CF compared to CT (p < 0.05). Significantly different soil N of 1.4 and 0.9 g kg−1 and available P of 6.7 and 4.1 ppm were recorded for PRB and CT, respectively. Higher straw and grain yield of 12 and 4.3, 10 and 3.5, 8 and 2.8 t ha−1 were recorded for PRB, CF and CT, respectively. Outputs of the PSEM highlighted two pathways in which CA‐based systems contributed to improved productivity: (a) via higher density of bacteria and improved hydraulic conductivity, and (b) via higher density of fungi and increase soil organic carbon content in the topsoil. The study concludes that CA‐based systems have the potential to improve crop productivity through improved soil health.